Career Maturity of Guidance and Counseling Students at University X: A Descriptive Study - Rolis; Chairun; Revayanti; Novita; Sufina (Era Scientific Publisher, 2026)
Career maturity is one of the important indicators of an individual's readiness to face the workforce. Students, as young individuals in the transitional phase between the educational world and the professional world, are expected to possess the ability to plan, explore, and make career decisions thoughtfully. This study aims to describe the level of career maturity among students based on the results of questionnaire analysis, as well as to identify aspects that need to be improved in the career development process. This study employs a descriptive quantitative approach involving 32 third-semester students from the Guidance and Counseling program at University X. The research instrument used is a Career Maturity Scale consisting of 25 statements, covering four main aspects: Career Planning, Career Exploration, Career Decision, and Knowledge of the Working World. The data were analyzed using descriptive statistics based on score norms from Indriyani (2020). The research results indicate that the majority of students have a high level of career maturity (87.50%), while 12.50% fall into the moderate category, and no respondents are in the low category. The Career Planning (90.63%) and Career Decision-Making (87.50%) aspects scored the highest, indicating that students have clear career directions and goals and are confident in making decisions. However, the Work Information aspect (31.25% high; 68.75% moderate) showed the lowest results, suggesting the need to enhance students' understanding of labor market dynamics and technological developments. Overall, this study confirms that students have good internal career readiness but still require reinforcement in external aspects through the provision of career guidance services, exposure to the industrial world, and improvement of digital career literacy.